Analisis Kepuasan Konsumen Dalam Menggunakan Jasa Pengiriman Paket Pos Optima Pada PT. Pos Indonesia (persero) Cabang Pontianak - Syarifah Arini (Universitas Muhammadiyah Pontianak, 2013)
Research to analyze customer satisfaction at optimal postal parcel delivery service at PT Pos Indonesia (Persero) Branch Pontianak. Dimension-imensi examined are reliability, responsiveness, assurance, empathy, and tangibles. This study used survey methods, data collection techniques, namely: observation, interviews, questionnaires, and documentation study. Samples used as many as 100 people by using purposive sampling. analysis using Cartesian diagram. The results of this study indicate that the majority of respondents were satisfied with the service of PT Pos Indonesia (Persero) Branch Pontianak with an average satisfaction level of 3.91 and the value of the average rate of interest of 4.34 dimension of service quality the most satisfied customers is assurance dimension and physical evidence, where the majority of respondents' votes are in quadrant B, which means that the interest and customer satisfaction are at a high level and in accordance with the wishes of the consumer. Dimensional quality of services that they are in quadrant A, which means the consumer is not satisfied then it should be further enhanced by the company. While the dimensions of the quality of services that are in quadrant C and D in which the interests of consumers are at a low level is considered normal practice even though consumers are satisfied because it is not very important.Keywords: Satisfaction, Service Quality Dimensions Services